2017
DOI: 10.20527/bipf.v5i1.2224
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Perangkat Pembelajaran Berorientasi Lingkungan Sekitar Bantaran Sungai Barito Untuk Melatihkan Keterampilan Proses Sains

Abstract: Pada proses perangkat pembelajaran  di sekolah dinilai masih kurang layak. Hal ini berimplikasi pada keterampilan proses sains dan hasil belajar kognitif siswa yang rendah. Untuk itu dilakukan pengembangan perangkat pembelajaran  menggunakan model inkuiri terbimbing yang memiliki tujuan khusus: (1) mendeskripsikan validitas perangkat pembelajaran, (2) mendeskripsikan kepraktisan perangkat pembelajaran yang ditinjau dari keterlaksanaan RPP, (3) Mendeskripsikan efektivitas perangkat pembelajaran yang ditinjau da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
6
0
3
Order By: Relevance
“…Student activities contained in teaching materials are arranged systematically and use Indonesian that is easily understood. This is in line with development research conducted which states that teaching materials that are arranged systematically can facilitate students in understanding learning through experiments [24].…”
Section: Methodssupporting
confidence: 85%
“…Student activities contained in teaching materials are arranged systematically and use Indonesian that is easily understood. This is in line with development research conducted which states that teaching materials that are arranged systematically can facilitate students in understanding learning through experiments [24].…”
Section: Methodssupporting
confidence: 85%
“…This evidenced by the large number of students who can answer the application of static fluid material in everyday life on learning achievement tests. This supported by the study by (I. N. Ihsan et al, 2017;, which shows that module developed by presenting problems that are close to students can improve student learning outcomes. Arends (2012) also revealed that giving issues taken in daily life support the achievement of learning objectives.…”
Section: Resultsmentioning
confidence: 59%
“…In addition, the RPP must also be designed according to the demands of the curriculum. RPP is a learning plan whose development refers to a certain basic competency in the curriculum or syllabus (Ihsan & Jamal, 2017), By developing a Lesson Plan following the curriculum, it will make the Lesson Plan more effective and efficient. What was found in the lesson plans revealed that the English teacher had designed indicators in the form of operational verbs and involved aspects of attitudes, aspects of knowledge, and aspects of skills.…”
Section: Discussionmentioning
confidence: 99%
“…A lesson plan is a written text compiled based on a systematic analysis of student development to make learning more effective and efficient by the demands of students and society (Sumantri, 2015). A lesson plan is a learning plan whose development refers to a certain basic competency in the curriculum or syllabus (Ihsan & Jamal, 2017) 13) Assessment of learning outcomes. Designing a lesson well will implement learning avoid mistakes.…”
Section: Introductionmentioning
confidence: 99%